Art as a Political Act: the Russian Agit-Props of the 1920s - Savaşır, Gökçeçiçek; Güleç, Ece (Süleyman Demirel Üniversitesi, 2020)
Emerged in the mid-19th century, the mechanical reproduction techniques changed the definitions of work of art, artist, and social role of art. These transformations have triggered an extensive sociocultural revolution during the 20th century. Art turned out to be an instrument for guiding the masses; and the communist ideology politicized aesthetics as a strategy of the power. The Russian Constructivists of the 1920s utilized agitation and propaganda techniques (agit-props) in their art for creating an aesthetic language for the political propaganda. This study argues that the Russian avantgarde aiming to bring art into everyday life and urban space became an instrument for aestheticization of politics. The scope is limited to the agit-props appropriated by the Bolshevik power. Dwelling on textual and visual documents from literature, it scrutinizes the topic with a historical interpretation research method. It aims to discuss the agit-props within the framework of politics and aesthetic revolution in everyday life and urban space.

19. yüzyılın ortalarında ortaya çıkan mekanik yeniden üretim teknikleri, sanat eserinin ve sanatçının tanımları ile sanatın toplumsal rolünü dönüştürmüş; 20. Yüzyıl boyunca sürecek geniş kapsamlı bir sosyo-kültürel devrimi de tetiklemiştir. Sanat, kitleleri yönlendirme aracına dönüşmüştür ve komünist ideoloji, iktidar stratejileri bağlamında estetiği siyasallaştırmıştır. 1920’lerin Rus Konstrüktivistleri sanatlarında, yeni bir estetik dil ve siyasi propaganda oluşturmak için ajitasyon ve propaganda tekniklerini (ajit-proplar) kullanmıştır. Bu çalışma, sanatı kente ve gündelik hayata katmayı amaçlayan Rus avangardının siyasetin estetikleştirilmesinde bir araç haline geldiğini savlamaktadır. Çalışmanın kapsamı, Bolşevik iktidar eliyle oluşturulmuş ajit-proplar ile sınırlandırılmıştır. Literatürden yazılı ve görsel kaynaklara başvuran çalışma, konuyu tarihselyorumlama araştırma yöntemiyle ele almaktadır. Ajit-propları, estetik-siyaset ilişkisi, kentsel mekânda ve gündelik hayatta estetik devrim çerçevesinde tartışmayı hedeflemektedir.
Politik Bir Eylem Olarak Sanat: 1920'lerdeki Rus Agit-prop Uygulamaları